Performance of Steel Frame with Linkage System under Earthquake Excitation - Xu, G.; Yamanari, M. (Engineering, Technology & Applied Science Research, 2019)
Authors have already proposed a linkage system with rotational friction dampers that can be expected to dissipate seismic energy rather than the main frame. In this paper, the relationship between the rotational angle of the linkage system and inter-story drift angle of a structure was investigated. Consequently, a three-bay twelve-story steel frame with linkage system was analyzed by a numerical simulation program based on a theory of non-linear dynamic analysis. The distribution of slipping moment of friction damper along with the height of the main structure was discussed. Meanwhile, optimal slipping moment range was suggested according to analysis results.